Enhancing the efficacy of collinear optical rectification for broadband THz radiation at MHz repetition rates - Buchmann, Tobias Olaf; Kelleher, Edmund John Railton; Zhou, Binbin; Jazbinsek, Mojca; Kwon, O. Pil; Seok, Jin Hong; Rotermund, Fabian; Jepsen, Peter Uhd (Optics InfoBase Conference Papers, 2020)
We demonstrate an optical-to-THz energy conversion efficiency of 5.5 10-4, by pumping the organic crystal HMQ-TMS with the externally compressed output of a Yb:fibre laser, enabling several kV/cm field strengths at MHz repetition rates.
Keywords: Broadband THz radiation; Energy conversion efficiency; Field strengths; Optical rectifications; Optical-; Organic crystal; Repetition rate; Yb fiber lasers